Analysis Of Transformational Leadership In Driving Employee Performance And Welfare Of Balo'ta Savings And Loan Cooperative Members, Berau Branch, East Kalimantan - Paembonan, Harlim; Pasae, Yoel; Baharuddin, Baharuddin (Jurnal Indonesia Sosial Sains, 2025)
This study aims to analyze the role of branch leaders with transformational leadership in encouraging employee performance and member welfare at the Balo'ta Savings and Loan Cooperative Berau Branch, East Kalimantan. The background of this research is based on the importance of leadership quality by branch leaders in encouraging employee performance or productivity and supporting the success of cooperatives in encouraging the welfare of their members. This study uses a qualitative method with a descriptive-analytical approach. Data collection techniques are carried out through in-depth interviews with leaders, employees, and cooperative members, direct observation in the field, and analysis of relevant documents. Source triangulation techniques are used to improve the validity of the data. Data analysis is carried out qualitatively with the stages of data reduction, data presentation, data validity test through data triangulation, and conclusion drawn. The results of this study show that transformational leadership not only drives employee performance internally, but also improves service quality and member satisfaction, which directly impacts improving the welfare of cooperative members. Therefore, transformational leadership has proven to be a central factor in driving better employee performance as well as member well-being